2021
DOI: 10.1002/mar.21587
|View full text |Cite
|
Sign up to set email alerts
|

The personalization–privacy paradox at the nexus of social exchange and construal level theories

Abstract: Marketing personalization requires firms to collect information that they can use to personalize their products or services, which might raise consumer privacy concerns. Prior studies on construal level theory suggest that happier Internet users would likely take future rewards in social exchanges (e.g., personalization–privacy trade‐offs) into greater consideration. Building on both social exchange and construal level theories, this article investigates the extent to which happiness with the Internet drives t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 144 publications
(208 reference statements)
1
48
0
Order By: Relevance
“…The more recent development of the Social Exchange Theory approach to understanding the relationship between privacy and "goods" production has shown that it can successfully combine several theories. For instance, Cloarec et al (2021) add Construal Level Theory (Liberman & Trope, 1998) While such a phenomenon has been documented in other contexts (e.g., healthy vs. vice foods; Laran, 2010;Wertenbroch, 1998), it is novel in the domain of privacy.…”
Section: Privacy and Personalization Of Products And Servicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The more recent development of the Social Exchange Theory approach to understanding the relationship between privacy and "goods" production has shown that it can successfully combine several theories. For instance, Cloarec et al (2021) add Construal Level Theory (Liberman & Trope, 1998) While such a phenomenon has been documented in other contexts (e.g., healthy vs. vice foods; Laran, 2010;Wertenbroch, 1998), it is novel in the domain of privacy.…”
Section: Privacy and Personalization Of Products And Servicesmentioning
confidence: 99%
“…"Consumers" decision-making process differs from hedonic and utilitarian products (Roggeveen et al, 2015), online and offline (Scarpi, 2012). Furthermore, recent works have related hedonism and utilitarianism to Construal Level Theory (Scarpi, 2021a(Scarpi, , 2021b, which has been proven to increase the explanatory power of Social Exchange Theory (Cloarec et al, 2021). Thus, hedonism and utilitarianism appear to be possible integrations to the Social Exchange Theory framework for understanding the trade-off between disclosing personal information and gaining personalization benefits.…”
Section: Privacy and Personalization Of Products And Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of the Internet economy, a large number of products have flooded into the e-commerce market, so that the intelligent recommendation has once again pushed to the wind ( Cloarec et al, 2022 ). Although the development of the e-commerce industry is in full swing, even so, the development of many traditional e-commerce platforms is not ideal, these traditional e-commerce platforms cannot guarantee to provide comprehensive user analysis, and mining user needs to provide the ideal recommendation program, and the lack of close contact between the user and the platform ( Cahyono et al, 2018 ; Cheng et al, 2019 ; Huang and Rust, 2021 ).…”
Section: Introductionmentioning
confidence: 99%